THE STABILITY OF FISH OIL JAMBAL SIAM (Pangasius hypopthalmus) IN PLASTIC BOTTLES AND GLASS DURING STORAGE - Lia Resti; Mirna Ilza; Edison ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was intended to determine the stability of fish oil jambal siam plastic bottles and glass during storage. The using of research method was experimental method is thend performed the analysis of the number of freee fatty acids and peroxidae value is the interval of 0, 10, 20, 30 and 40 days. Data were analyzed using t-test. To see the effect of storage time on the content of free fatty acids and peroxide content of regression analysis. Meanwhile, to measure the closeness of his relationship conducted correlation analyzes. The ingredient of study are fatty fish jambal siam obtained from market arengka Pekanbaru as much 3 kg. Then the fish oil is packaged in plastic bottles and glass bottles. The study states there are differences in the stability of fish oil jambal conjoined in plastic bottles and glass. Fish oils are stored in glass bottles better than fish oil in plastic bottles, this is evidenced by the long correlation parameter storage degradation has a stronger relationship. Based on the analysis of free fatty acids and peroxide value analysis glass bottle is a bottle that best maintain the stability of fish oil jambal conjoined within the prescribed period of 40 days with an average free fatty acid content of 1.03% and an average content of peroxide 20,75meq / kg. Keywords: fish oil , catfish, shelf life, the type of packaging